Stress and fear in women living with cancer: An argumentation towards the adaptation theory - Ni Putu Wulan Purnama Sari (International Journal of Public Health Science (IJPHS), 2020)
Extended life expectancy in cancer nowadays has implication on longer exposures toward cancer-related stressors. Based on the adaptation theory, the longer the stressor exposures then the more the stress tolerance expected. This study aimed to compare and analyze the differences of stress and fear in cervical and breast cancer survivors (CCS and BCS) between cases and survivorship stages, impacting on anxiety, depression, and perceived life normality (PLN). This cross-sectional study involved 47 CCS and 58 BCS (n=105). Self-developed instrument was used in data collection (r=-0.256-0.935; Chronbach’s Alpha=0.908). Various statistical tests were used in data analysis (α<0.05). Stress due to cancer diagnosis and treatments were significantly different between cases (p=0.005 and p=0.003 in CCS and BCS respectively), impacting significant differences on anxiety, depression, and PLN between cases (p=0.025, p=0.000, and p=0.000 respectively). In both cases, stress due to cancer diagnosis and treatments, anxiety, depression, and PLN were not significantly different between survivorship stages (all p>0.05). Fear towards cancer recurrence, metastasis, additional cancer, and diagnostic test were not significantly different between cases and survivorship stages (all p>0.05). These findings argue the adaptation theory because the adaptation process was proved to be limitless in CCS and BCS; therefore it can’t be seen as a product.